Pagurus asper H. Milne Edwards, 1848, a subjective synonym of Clibanarius longitarsus (De Haan, 1849) and reversal of precedence (Crustacea: Decapoda: Anomura: Diogenidae) - Low, Martyn E. Y.; Rahayu, Dwi Listyo (Zootaxa, 2014)
The species-group name Pagurus longitarsus was proposed by De Haan (1849: 211, pl. 50, fig. 3) for a species of hermit crab collected from Japan (see Yamaguchi & Baba 1993: 272, 273). Dana (1852b: 464) transferred Pagurus longitarsus to the genus Clibanarius Dana, 1852 (first established in Dana 1852a). Dana (1852b: 464) also suggested that Pagurus longitarsus De Haan, 1849, and Pagurus asper H. Milne Edwards, 1848, were possibly synonymous by listing “Pagurus asper ? Edwards, Ann. des Sci. Nat., 1848(3), v. [sic] 62” in the synonymy of Pagurus longitarsus De Haan, 1849. Fize & Serène (1955: 72) repeated Dana’s (1852b: 464) opinion regarding the synonymy Pagurus longitarsus and Pagurus asper. McLaughlin (2002: 399) and McLaughlin et al. (2010: 20) also considered Pagurus longitarsus De Haan, 1849, and Pagurus asper H. Milne Edwards, 1848, to be possibly conspecific, but considered Clibanarius longitarsus (De Haan, 1849), to be the valid name.